Generation of Leishmania hybrids by whole genomic DNA transformation. - Adriano C Coelho; Philippe Leprohon; Marc Ouellette (Public Library of Science (PLoS), 2012)
Genetic exchange is a powerful tool to study gene function in microorganisms. Here, we tested the feasibility of generating Leishmania hybrids by electroporating genomic DNA of donor cells into recipient Leishmania parasites. The donor DNA was marked with a drug resistance marker facilitating the selection of DNA transfer into the recipient cells. The transferred DNA was integrated exclusively at homologous locus and was as large as 45 kb. The independent generation of L. infantum hybrids with L. major sequences was possible for several chromosomal regions. Interfering with the mismatch repair machinery by inactivating the MSH2 gene enabled an increased efficiency of recombination between divergent sequences, hence favouring the selection of hybrids between species. Hybrids were shown to acquire the phenotype derived from the donor cells, as demonstrated for the transfer of drug resistance genes from L. major into L. infantum. The described method is a first step allowing the generation of in vitro hybrids for testing gene functions in a natural genomic context in the parasite Leishmania.